PENGARUH MEDIA CELEMEK CERITA TERHADAP KEMAMPUAN BERBICARA PADA ANAK USIA 5-6 TAHUN DI TK IT BUNAYYA PEKANBARU - Khairun Nisa; Zulkifli N Zulkifli N; Yeni Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Depends on the observation towards childrens’ speaking skill, it is not optimal. So itt is need to give the application of option story modern. The purpose of this research is to know the effect of apron story media towards childrens’ speaking skill of 5-6 years old at TK IT Bunayya Pekanbaru. This research is using experimental method with one group pretest posttest design. The population of this research is the childrens’ of 5-6 years old with the total childrens’ is 82 childrens’ and the sample that have been used is non-probability sampling with random lottery. The samples of this research are 17 childrens’. The technique for collecting the data that have been used is observation. The data technique analysis that have been used is t-test. The result of this hypothesis research is 17,888 with Sig. (2-tailed) = 0,000<0,05 means that there is the defferences of the childrens’ speaking skill after this research. The effect of apron story media towards childrens’ speaking skill of 5-6 years old at TK IT Bunayya Pekanbaru is 57,77% and it is counted as average category.Key Words: Spesking Skill, Apron Story Media.